Digital agribusiness - 5 recommendations for ICT4Ag entrepreneurs - Lohento, Ken (Technical Centre for Agricultural and Rural Cooperation, 2018)
Ken Lohento, Senior Programme Coordinator at CTA, makes five recommendations to digital agricultural entrepreneurs regarding their business model.